A two steps Lagrangian–Eulerian numerical model for the simulation of explosive welding of three dissimilar materials joints. (November 2021) - Campanella, Davide; Buffa, Gianluca; Fratini, Livan
Abstract: Explosion welding (EXW) is a solid-state joining process used to produce lap joints out of metal plates of dissimilar materials. During the process, a controlled explosive detonation results in a pressure wave pushing one of the plates to be welded, called flyer, against the other with high velocity. The high pressure and temperature generated, because of the impact energy decaying into heat, create the conditions for solid bonding phenomenon to take place. Due to the complexity of experimental tests, numerical simulation is considered a fundamental design tool for the process. Different approaches are found in literature to simulate the process. In this paper, a dual step Lagrangian–Eulerian approach is proposed to evaluate the effect of different explosives on the final quality of the weld. The numerical model was developed using the commercial software ABAQUS. A three dissimilar materials joint is considered, made of two outer plates of AA5083 aluminum alloy and A516 steel, respectively, and an intermediate layer made of AA1050 aluminum alloy. The model was first validated by comparing the wavy profile of the intermediate layer after the weld, and then used to evaluate the effect of different explosive by analyzing the distribution of the main process parameters as well as the presence of voids.